Transformational Leadership: an Overview and Bibliometric Analysis - Mochammad Bachtiar Affandie; Madziatul Churiyah (CV. Syntax Corporation Indonesia, 2022)
The purpose of this research is to examine the discussion of transformational leadership. This review analyzes 6877 articles found and extracted into 646 scientific articles from the Scopus database during the period 2018 – 2022 with bibliometric analysis techniques using VOSviewer software. The results of the analysis have identified the most active and influential co-authorship, co-accurance, and citations in this field. The elaboration and visualization of the origin mapping where keyword analysis will occur conveys developments on the topic of transformational leadership. This literature study can be a source of reference for further research on the topic of transformational leadership and relationships using other key terms.